INFORMATION RETRIEVAL OF AUDIOVISUAL (VIDEO) COLLECTIONS TO SUPPORT LEARNING AT SUNAN KALIJAGA STATE ISLAMIC UNIVERSITY LIBRARY - Simatupang, Abdul Rahman; Siregar, Halimatussa'diyah (Academic Solution Publisher, 2025)
This article aims to examine the digital collection retrieval system—particularly video collections—in academic libraries and its relationship to the teaching–learning process. This study employs a descriptive research method. Data were collected through observation and a review of the relevant literature. The descriptive analysis is presented in narrative form. The findings indicate that developing an effective retrieval system requires identifying user needs, designing an appropriate database system, and conducting continuous evaluation. In the learning process, a well-designed video collection retrieval system significantly supports users in meeting their information needs.